Between Special and Regular Settings: The Teachers Attitude towards Inclusion - Khofidotur Rofiah (International Inclusion Development and Cooperation, 2022)
A large number of teachers have expressed concern about their ability to meet the educational needs of students with disabilities in general education classes. For the time being, there is little evidence to support the divergent opinions on inclusive education held by general and special education teachers. The purpose of this study is to investigate the attitude towards inclusive education held by general and special education teachers in Indonesia. Multidimensional Attitudes toward Inclusive Education Scales (MATIES) will be used to examine the attitudes about inclusive education. It consists of 18 items that are designed to test the emotive, cognitive, and behavioral elements of attitudes toward inclusion in an effective manner. Using Google Forms, the instruments were sent to participants through the internet survey platform. The T-Test and ANNOVA test was used to evaluate the data.